Uterine rupture at 33rd week of gestation after laparoscopic myomectomy with signs of fetal distress. A case report and review of literature - Hiroyuki Yazawa; Kaoru Takiguchi; Fumihiro Ito; Keiya Fujimori (Elsevier, 2018)
Objective: We describe a case of uterine rupture (UR) during pregnancy after laparoscopic myomectomy (LM) and discuss the risk factors of UR. Case report: A 37-year-old woman with multiple myomas underwent laparoscopic myomectomy. Subserosal and intramural myomas were enucleated, and the myometrial wounds were repaired with single-layer suturing. Sixteen months after the operation, the patient conceived. At 33 weeks of gestation, emergency cesarean section was performed for the indication of fetal distress. A male neonate was delivered without asphyxia. During cesarean section, surgeons identified a 2 × 3 cm myometrial defect at one of the myomectomy sites, and diagnosed incomplete UR. The myometrial defect was repaired with debridement and suturing. Conclusion: Based on the literature review, the risk of UR during pregnancy after LM is estimated to be less than 1% when all the surgical procedures have been performed appropriately. Myomectomy should be performed with careful consideration by surgeons who have good knowledge of the wound healing process in the myometrium. Keywords: Laparoscopic myomectomy, Uterine rupture, Risk factor, Fetal distress, Pregnancy